2017
DOI: 10.5898/jhri.6.3.deligianis
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Intergroup Bias on Trust and Approach Behaviour Towards a Humanoid Robot

Abstract: As robots become commonplace, and for successful human-robot interaction to occur, people will need to trust them. Two experiments were conducted using the "minimal group paradigm" to explore whether social identity theory influences trust formation and impressions of a robot. In Experiment 1, participants were allocated to either a "robot" or "computer" group, and then they played a cooperative visual tracking game with an Aldebaran Nao humanoid robot as a partner. We hypothesised participants in the "robot g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 64 publications
(75 reference statements)
1
14
0
Order By: Relevance
“…Deligianis et al discovered that people were willing to trust robots when it meant accomplishing a more difficult task with their help [41]. The study of attitudes towards humanoids in the care of older adults held by particular age groups is important because the process of technology development seems to be relatively long and its implementation on a mass scale might be seen by the current generation of the youngest citizens.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Deligianis et al discovered that people were willing to trust robots when it meant accomplishing a more difficult task with their help [41]. The study of attitudes towards humanoids in the care of older adults held by particular age groups is important because the process of technology development seems to be relatively long and its implementation on a mass scale might be seen by the current generation of the youngest citizens.…”
Section: Resultsmentioning
confidence: 99%
“…A literature review by Deligianis et al indicated that the ability to generate and maintain trust is of paramount importance in human-robot interaction [41]. Three groups of factors influence the trust formation: a human, a robot, and an environment [42].…”
Section: Doll Robot Babyloidmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants who were assigned into a "blue" group together with a robot showed an extent of anthropomorphic inferences about the robot and more positive evaluations compared to participants in the condition where the robot was not in the same group [46]. Similarly, intergroup bias can significantly affect how close humans are approaching an ingroup robot and how much they trust the robot's suggested answers with respect to task difficulty [19]. However, this research on perception of robot groups (online studies) and minimal group paradigms (one robot grouped with one human) has so far not been conducted in group settings that go beyond the dyad.…”
Section: How Humans Perceive Robot Groupsmentioning
confidence: 97%
“…Participants who were assigned into a blue group together with a robot showed an extent of anthropomorphic inferences about the robot and more positive evaluations compared to participants in the condition were the robot was not in the same group [21]. Similarly, intergroup bias can significantly affect how close humans are approaching an in-group robot and how much they trust the robots suggested answers with respect to task difficulty [22]. However, this research on perception of robot groups (online studies) and minimal group paradigms (one robot grouped with one human) has so far not been conducted in group settings that go beyond the dyad.…”
Section: How Humans Perceive Robot Groupsmentioning
confidence: 99%